Pengalaman Single Parent dalam Mengasuh Anak Usia Pra-Sekolah (6 Tahun) - Mochamad Heri; Agus Ari Pratama; I Gede Agus Sastra Wijaya (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the experience of a single parent in caring for preschool-aged children (6 years) in the District of Buleleng. The research method used in this study is qualitative research with a phenomenological approach. The results of this study used in-depth interviews using collaizi analysis, which resulted in 3 themes: the causes of single parenting, the obstacles experienced after becoming a single parent, and the impact of single parents in parenting. In conclusion, the results of this study for single parents can increase knowledge about the struggles of a single parent. Keywords: Children, Experience, Parenting, Single Parent